Analisa Pengaruh Biaya Produksi Terhadap Barang yang dihasilkan pada Perusahaan Garment - Amalia Amalia; Sukemi Kamto Sudibyo (MANAJEMEN, 2026)
This study aims to empirically examine the effect of production costs on the volume of goods produced in the garment industry, a manufacturing sector characterized by a high level of dependence on fluctuations in production inputs. In this study, production costs are classified into three main components: direct raw material costs, direct labor costs, and factory overhead costs. The primary issue addressed is the uncertainty of profit margins resulting from escalating material prices and minimum wage regulations, both of which directly affect the company’s production capacity. The research employs a quantitative approach with a causal research design. Secondary data were collected from the annual financial reports of garment companies over a specific observation period. Data analysis was conducted using multiple linear regression techniques to examine the significance of the effects, both partially and simultaneously. From a theoretical perspective, efficiency in the allocation of production costs is expected to optimize the quantity of goods produced without compromising established quality standards. The findings are projected to indicate that raw material costs exert the most dominant influence on production output, while labor costs also demonstrate a significant yet elastic effect on operational efficiency. This study concludes that the synchronization between production budget planning and targeted output volume is highly essential for maintaining productivity stability and enhancing the company’s competitiveness in the global market.